A New Class of Tunable Dendritic Diphosphine Ligands: Synthesis and Applications in the Ru-Catalyzed Asymmetric Hydrogenation of Functionalized Ketones - Ma, Baode; Miao, Tingting; Sun, Yihua; He, Yanmei; Liu, Ji; Feng, Yu; Chen, Hui; Fan, Qing-Hua (Chemistry : a European journal, 2014)
A series of tunable G0–G3 dendritic 2,2′‐bis(diphenylphosphino)‐1,1′‐binaphthyl (BINAP) ligands was prepared by attaching polyaryl ether dendrons onto the four phenyl rings on the P atoms. Their ruthenium complexes were employed in the asymmetric hydrogenation of β‐ketoesters, α‐ketoesters, and α‐ketoamides to reveal the effects of dendron size on the catalytic properties. The second‐ and third‐generation catalysts exhibited excellent enantioselectivities, which are remarkably higher than those obtained from the small molecular catalysts and the first‐generation catalyst. Molecular modeling indicates that the incorporation of bulky dendritic wedges can influence the steric environments around the metal center. In addition, the ruthenium catalyst bearing a second‐generation dendritic ligand could be recycled and reused seven times without any obvious decrease in enantioselectivity. Dendron tuning: A series of tunable dendritic BINAP ligands was prepared by attaching polyaryl ether dendrons onto the four phenyl rings on the P atoms and successfully applied in the Ru‐catalyzed asymmetric hydrogenation of β‐ketoesters, α‐ketoesters, and α‐ketoamides (see figure). The dendritic wedges were found to be able to effectively tune the asymmetric induction of the catalysts and excellent enantioselectivities were observed with the larger dendrimers.